Effects of a free school breakfast programme on school attendance, achievement, psychosocial function, and nutrition: a stepped wedge cluster randomised trial - Maddison Ralph; Michie Jo; Jiang Yannan; Gorton Delvina; Turley Maria; Ni Mhurchu Cliona; Hattie John (BMC, 2010)
Abstract Background Approximately 55,000 children in New Zealand do not eat breakfast on any given day. Regular breakfast skipping has been associated with poor diets, higher body mass index, and adverse effects on children's behaviour and academic performance. Research suggests that regular breakfast consumption can improve academic performance, nutrition and behaviour. This paper describes the protocol for a stepped wedge cluster randomised trial of a free school breakfast programme. The aim of the trial is to determine the effects of the breakfast intervention on school attendance, achievement, psychosocial function, dietary habits and food security. Methods/Design Sixteen primary schools in the North Island of New Zealand will be randomised in a sequential stepped wedge design to a free before-school breakfast programme consisting of non-sugar coated breakfast cereal, milk products, and/or toast and spreads. Four hundred children aged 5-13 years (approximately 25 per school) will be recruited. Data collection will be undertaken once each school term over the 2010 school year (February to December). The primary trial outcome is school attendance, defined as the proportion of students achieving an attendance rate of 95% or higher. Secondary outcomes are academic achievement (literacy, numeracy, self-reported grades), sense of belonging at school, psychosocial function, dietary habits, and food security. A concurrent process evaluation seeks information on parents', schools' and providers' perspectives of the breakfast programme. Discussion This randomised controlled trial will provide robust evidence of the effects of a school breakfast programme on students' attendance, achievement and nutrition. Furthermore the study provides an excellent example of the feasibility and value of the stepped wedge trial design in evaluating pragmatic public health intervention programmes. Trial Registration Number Australian New Zealand Clinical Trials Registry (ANZCTR) - ACTRN12609000854235